Dynamics of Community Formation Developing Identity and Notions of Home (Palgrave Macmillan US, 2018)
This interdisciplinary work discusses the construction, maintenance, evolution, and destruction of home and community spaces, which are central to the development of social cohesion. By examining how people throughout the world form different communities to establish a sense of home, the volume surveys the formation of identity within the context of rapid development, global and domestic neoliberal and political governmental policies, and various societal pressures. The themes of cooperation, conflict, inclusion, exclusion, and balance require negotiation between different actors (e.g., the state, professional developers, social activists, and residents) as homes and communities develop. .